Determinants of Stunting Events in Children Aged 6-23 Months in Locus and Non-Locus Areas in East Luwu Regency - Kanaang Mabe Parenreng; Veni Hadju; Burhanuddin Bahar; Nurhaedar Jafar; Healthy Hidayanty; Lalu Muhammad Saleh (Journal La Medihealtico, 2020)
Nationally, the prevalence of stunting in children under five in Indonesia is 30.8%. The incidence of stunting varies from region to region. This study aims to determine the determinants of stunting in children aged 6-23 months in the locus and non-loci in East Luwu Regency. This research is an observational analytic study using a cross sectional design. The study population was 858 children aged 6-23 months in five locus villages and five non-locus villages. A sample of 200 people was taken using purposive sampling method, data were analyzed using the chi square test and logistic regression using the SPSS application. The results showed the similarity in terms of parental education in both regions. In general, the father has a job and the mother is a housekeeper. Income levels are higher in locus areas. As much as 43.1% of baduta had stunting at locus area and 22.4% at non locus. The logistic regression test showed that the factors associated with stunting in the locus were family members smoking (p = 0.032), hand washing practices (p = 0.036) and exclusive breastfeeding (p = 0.001). Meanwhile, non-locus areas were a history of diarrhea disease (p = 0.049) and hand washing practices (p = 0.052). Combined analysis of locus and non-loci showed that family members smoking (p = 0.005), exclusive breastfeeding (p = 0.001), frequency of complementary feeding (p = 0.027) and hand washing practices (p = 0.001) were determinants of stunting. The most dominant variable in the locus was exclusive breastfeeding, while non-locus was a history of diarrhea. Conclusion: The determinants of locus stunting are family members smoking, hand washing practices and exclusive breastfeeding. Meanwhile, non-locus areas are a history of diarrhea disease and hand washing practices.